Usefulness of iodine-123 whole-body scan in planning iodine-131 treatment of the differentiated thyroid carcinoma in children and adolescence. Issue 12 (December 2018) - Villani, Maria F.; Grossi, Armando; Cassano, Bartolomeo; Pizzoferro, Milena; Ubertini, Graziamaria; Longo, Mariaconcetta; Garganese, Maria C.
Abstract : Objective: Radioiodine treatment (RAI-T) of differentiated thyroid carcinoma (DTC) is important to avoid disease progression, in particular in pediatric patients. For these reasons, a diagnostic scan may be useful to assess therapeutic tailored activity. The purpose of our study was to evaluate the usefulness of diagnostic whole-body scan (WBS) with iodine-123 ( 123 I) in combination with recombinant human thyroid-stimulating hormone (rh-TSH; Thyrogen) (rh-TSH-Dx-WBS), in planning RAI-T or further surgery before RAI-T in pediatric DTC. Patients and methods: Among 101 rh-TSH-Dx-WBS of 55 patients (21 males, mean age: 15 years, range: 5–18 years) followed at the Bambino Gesù Pediatric Hospital for DTC from February 2004 to December 2016, 41 rh-TSH-Dx-WBS scans of 41 patients (20 male and 21 female, mean age: 14 years, range: 5–18 years) performed for staging before RAI-T were retrospectively evaluated. Thyroglobulin was determined at baseline and on day 5. Results: Receiver operating characteristic curve analysis showed that thyroglobulin alone is not a good predictor for staging modification (area under the curve=0.6855). rh-TSH-Dx-WBS showed both remnant and lymph node in 11 (27%), lymph node localization alone in one (2.5%), lung alone in 1/41 (2.5%), both lymph node and lungs in 2/41 (5%), and thyroid remnant alone in 26/41 (63%) patients. rh-TSH-Dx-WBS modified staging in 12/41 (29%): in 3/12 (25%) for the presence of lung metastases and in 9/12 (75%) for lymph node involvement. In all these patients, administered activity for RAI-T was then modified or further surgery was planned. Conclusion: Although further studies are needed, our data showed that combined use of rh-TSH and 123 I-Dx-WBS allows an accurate and complete staging of disease, to implement the best therapeutic plan.